Pasang-Surut Komitmen Kebangsaan - Yudi Latif (Budapest International Research and Critics University, 2014)
Our national commitment can be seen through three phases, namely in the early days of independence, in the New Order era, and in the Reform Era. Our national commitment at the beginning of the independen- ce is scratched as negative-defensive nationalism force, when it was faced with a common enemy from outside (colonization). Our national commit- ment in the New Order era is marked by making economy as the comman- der in terms of growth, stability and centralization of power, bringing a variety of inequality. The most striking, there is lack of harmony between the national and statehood character. National multicultural character of Indonesia was denied by the centralized nature of waking state. Imbalance between central and local government with denial of political, social, eco- nomic and cultural rights of local communities. Meanwhile, the national commitment in the Reformation Era is characterized by openness and free- dom of public space that brings euphoria for the expression of marginalized identities. Efforts to bring diversity of expression